Penerapan Sistem Pakar pada Diagnosa Penyakit Gerd (Lambung) Menggunakan Metode Case Based Reasoning - Alsyira, Mukhfika; Fithry Tahel (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Gastroesophageal Reflux Disease (GERD) is a common digestive disorder, which can cause symptoms such as chest pain, acid regurgitation, and sleep disturbances. In an effort to improve the diagnosis of GERD disease efficiently, this study proposes the development of an expert system using the Case-Based Reasoning (CBR) method. The system aims to diagnose GERD based on previous cases that have been recorded on a case basis. The main steps in system development include data acquisition, knowledge representation, case similarity assessment, and problem solving. This research combines CBR approach with data mining techniques to obtain a more accurate assessment. System testing was performed using existing patient datasets, and the results showed that the system can provide a diagnosis of GERD with a high degree of accuracy. This research offers a significant contribution to the medical field in improving the process of diagnosis and management of GERD disease efficiently and effectively.